1997
DOI: 10.1046/j.1471-4159.1997.68010176.x
|View full text |Cite
|
Sign up to set email alerts
|

Coloboma Hyperactive Mutant Mice Exhibit Regional and Transmitter‐Specific Deficits in Neurotransmission

Abstract: The mouse mutant coloboma (Cm/+), which exhibits profound spontaneous hyperactivity and bears a deletion mutation on chromosome 2, including the gene encoding synaptosomal protein SNAP‐25, has been proposed to model aspects of attention‐deficit hyperactivity disorder. Increasing evidence suggests a crucial role for SNAP‐25 in the release of both classical neurotransmitters and neuropeptides. In the present study, we compared the release of specific neurotransmitters in vitro from synaptosomes and slices of sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
1
1

Year Published

2000
2000
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(50 citation statements)
references
References 73 publications
0
48
1
1
Order By: Relevance
“…Interestingly, coloboma mice have a 2 cM deletion on chromosome 2, including the SNAP25 gene. 32 Raber et al 12 studied the release of several neurotransmitters in heterozygous mice (Cm/ þ ), expressing 50% of the SNAP25 protein level, and showed that depolarisation failed to induce dopamine release and induced significantly lower than normal amounts of serotonin from the dorsal striatum. These results were recently confirmed by Fortin et al, 43 who showed that SNAP25 was required for dopamine release from rat neurons in culture.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, coloboma mice have a 2 cM deletion on chromosome 2, including the SNAP25 gene. 32 Raber et al 12 studied the release of several neurotransmitters in heterozygous mice (Cm/ þ ), expressing 50% of the SNAP25 protein level, and showed that depolarisation failed to induce dopamine release and induced significantly lower than normal amounts of serotonin from the dorsal striatum. These results were recently confirmed by Fortin et al, 43 who showed that SNAP25 was required for dopamine release from rat neurons in culture.…”
Section: Discussionmentioning
confidence: 99%
“…First, SNAP25 is a presynaptic plasma membrane protein essential for the triggering of vesicular fusion and neurotransmitter release. 12,13 Second, postmortem studies have shown modifica-tions of SNAP25 protein levels in some brain regions of bipolar patients. 14,15 Third, SNAP25 gene has been widely associated with attention-deficit hyperactivity disorder (ADHD), which is known to share genetic susceptibility with early-onset BD.…”
Section: Introductionmentioning
confidence: 99%
“…The SNAP-25 protein is essential for the fusion of the neurotransmitter vesicle with the presynaptic membrane in order to release neurotransmitters. This might explain why the DA release in the dorsal striatum of the coloboma mutant mouse is almost completely lost (Raber et al 1997). In addition, the D 2 receptor expression is increased in the ventral tegmental area and substantia nigra (Jones et al 2001b).…”
Section: The Coloboma Mutant Mousementioning
confidence: 99%
“…8 Fourth, deletion of SNAP25 is responsible for the behavioral alterations found in coloboma mice, an animal model of ADHD. [9][10][11] The clinical features of ADHD overlap with the symptoms of mania and hypomania. Finally, a decrease in SNAP-25 and synaptophysin proteins has been found in the brains of schizophrenics.…”
Section: Introductionmentioning
confidence: 99%